3D Neural Spheroids: Surface‐Functionalized Self‐Standing Microdevices Exhibit Predictive Localization and Seamless Integration in 3D Neural Spheroids (Adv. Biosys. 11/2020). Issue 11 (27th November 2020) - Lecomte, Aziliz; Giantomasi, Lidia; Rancati, Silvia; Boi, Fabio; Angotzi, Gian Nicola; Berdondini, Luca
Abstract : In article number 2000114, Luca Berdondini and co‐workers present 3D neurospheroids with self‐standing silicon microdevices internalized at different levels. Results are obtained by uncovering the control capability of silicon surface engineering to drive microdevices at predefined sites during cellular aggregation and 3D growth. This work paves the way to bionic brain‐tissue models with inbuilt untethered bioelectronic sensors and actuators.